GMAT Club

Kudos owned by the user


JeffTargetTestPrep received 4 Kudos for post Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b).

GiverPostDate
Shaan6848Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)26-Aug-2023
Kimberly77Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)29-Oct-2022
delta23Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)05-Aug-2018
biyanianujRe: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)30-Sep-2017

Page 1 of 1